Physiological responses and post - stress recovery in field - grown maize exposed to high temperatures at flowering - Neiff, Nicolás (2019)
Fil: Neiff, Nicolás. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias. Departamento de Producción Vegetal. Corrientes, Argentina.